Présence du végétal dans The Golden Apples de Eudora Welty - Jean-Marc Victor (Sillages Critiques)
This article proposes to examine Eudora Welty’s short story cycle The Golden Apples (1949) in the light of the links (both explicit and secret) between this peculiar narrative form and various questions pertaining to botany : classification, dissemination, proliferation, pollinization, among others.